Monthly changes in tissue weight and biochemical composition of the musel Mytella guyanensis (Bivalvia: Mytilidae) in Costa Rica - Cruz, Rafael A (1993)
Monthly changes in body weight and biochemical composition of Mytella guyanensis were studied in Nicoya, Costa Rica, (May 1989-Aprill990). Dry tissue weight was minimal in December and rose to a peak in luly, in accordance to periods of maturation and apawning. Mean percentage values of the main components of dry flesh were: proteína 58.3, carbohydrates 22.8,lipida 7.2 and ash 11.2. The mean caloric value of dry flesh was 5.2 KcaVg. Decrease in the percentage of lipids, proteíns and caloric values coincided witb the spawnig periodo